GRADUASI MANDIRI: BENTUK KEBERDAYAAN PENERIMA MANFAAT (KPM) PROGRAM KELUARGA HARAPAN (PKH) DI KABUPATEN PATI - Khoiriyah, Nur; kunarti, Kunarti (KOMUNITAS, 2019)
Independent graduation, is a phenomenon of resignation from PKH program membership. This is different from some other social ministry programs. Programs that encourage the empowerment of beneficiary communities. Based on this uniqueness, this study specifically examines how the condition of PKH participants before and after graduation, as well as looking for forms of empowerment that are owned by PKH Graduasi Mandiri participants. Field findings indicate the empowerment process carried out by PKH facilitators through regular monthly meetings. Assistance is filled with the delivery of empowerment material. Materially, not much amount of assistance was received, but the assistance was carried out continuously. The form of KPM PKH empowerment after independent graduation can be seen through five indicators, including freedom of mobility, ability to buy small commodities, being involved in household decision making, having relative freedom from family domination, and having economic security and contribution to the family.